Robert Baine papers - Baine, Robert
Account book (1758) and ship's log (1759) for the ship Peggy of Glasgow on a trip from Clyde, Scotland to Williamsburg, Louisa, and Richmond, Va. Includes letterbook fragments (1759).
Merchant, businessman, and shipowner.
Collection material in English.
Keywords: Peggy of Glasgow (Ship); Merchants -- Virginia -- Louisa; Merchants -- Virginia -- Williamsburg; Merchants -- Virginia -- Richmond; Ship's papers -- 18th century; Scotland -- Commerce; Merchants -- Scotland -- Greenock; Businessmen; Merchants; Shipowners